Efficacy of Probiotics on Survival, Growth, Biochemical Changes and Energy Utilization Performance of Macrobrachium rosenbergii (De Man 1879) Post-larvae - Seenivasan, C.; Radhakrishan, S.; Muralisankar, T.; Bhavan, P. S. (Journal of Scientific Research, 2012)
The efficacy of combined probiotics, Lactobacillus sporogenes and Saccharomyces cerevisiae (LS+SC) on survival, growth, biochemical changes and energy utilization of Macrobrachium rosenbergii post larvae (PL) was examined. Each probiotic organism was individually tested at four different concentrations (1-4%) separately. The best concentration in each probiotic species was combined and tested for its suitability in aquaculture usage. The basal diet was incorporated with probiotics, LS+SC (4:4) at five different concentrations 0% (control), 1%, 2%, 3% and 4%. These diets were fed to M. rosenbergii PL for a period of 90 days. After the feeding trail, 2% LS+SC incorporated diet had significantly (P<0.05) higher survival, WG, SGR, FCE and PER compared with other experimental groups than the control. Whereas, the FCR was significantly (P<0.05) lower in 2% LS+SC incorporated diet fed PL. Similarly the proximate composition of the protein, amino acid, carbohydrate, lipid and ash content were significantly (P<0.05) higher in 2% LS+SC incorporated diet fed PL than the control. The energy utilization parameters were significantly (P<0.05) higher in 2% LS+SC incorporated diet fed PL than the control. This study indicated that combined probiotics, LS+SC incorporated diets were beneficial for M. rosenbergii in terms of increasing growth and enhancing energy utilization performances. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.10193 J. Sci. Res. 4 (3), 729-740 (2012)